Expression of calcium-binding proteins S100A8, S100A9 and S100A12 in otitis media. (October 2017) - Hong, Wenzhou; Khampang, Pawjai; Samuels, Tina L.; Kerschner, Joseph E.; Yan, Ke; Simpson, Pippa
Abstract: Objectives: Calgranulins (calcium-binding proteins S100A8, S100A9 and S100A12) are predominant cytoplasmic proteins of neutrophils and produced by various cells, playing multiple functions in innate immunity and the inflammatory process. Although up-regulated expression of S100A8 and S100A9 genes were observed in an animal model of otitis media (OM), their expressions have not been studied in human middle ear epithelial cells in response to the OM pathogen or in patients with recurrent or chronic OM (recurrent OM/RecOM or chronic OM with effusion/COME). Study design: Gene expressions were compared between Streptococcus pneumoniae (SP)-infected and non-infected human middle ear epithelial cells (HMEECs) as well as between chronic OM patients and control patients (CI). Methods: Gene expressions were profiled by quantitative real time PCR (qPCR). S100 proteins in OM patient and CI middle ear biopsies were detected by immunostaining. Results: S100A8, S100A9 and S100A12 gene expressions were elevated in SP-infected HMEECs in time-dependent manner. S100A8 and S100A9 but not S100A12 gene expression was significantly elevated in the middle ear mucosa of OM patients. S100A8 and S100A9 protein were observed in middle ear mucosa of OM, but not CI patients. Minimal co-localization was observed between S100A8 and S100A9 with neutrophil elastase and cytokeratin in ME sections of OM patients. Conclusion: Elevated S100A8 and S100A9 gene expression in SP-infected HMEECs and in the middle ear mucosa of OM, minor co-localized with neutrophil markers suggests that middle ear epithelial cell secretion of S100A8 and S100A9 may play a role in the pathogenesis of recurrent and chronic OM.